Pengaruh Metode Teams Games Tournament (TGT) terhadap Hasil Belajar Siswa pada Mata Pelajaran PAI - Siti Kurniawati; Santi Lisnawati; Sutisna (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to determine the influence of the Teams Games Tournament (TGT) learning method on student learning outcomes in Islamic Religious Education subjects at SMAN 10 Bogor. This research includes experimental research. The population in this study included all class XI students at SMAN 10 Bogor consisting of 8 classes. Then from this population two classes were taken randomly to be used as research samples, namely class XI F as the experimental class and class XI H as the control class consisting of 30 students in each class. The instrument in this research uses pre-test and post-test questions that have been validated by experts, namely PAI subject teachers. Based on the research results, the average score obtained for the experimental class after treatment using the Teams Games Tournament method was 84.33. Meanwhile, the average score for the control class was 61.67. Next, it was tested using the t test with the SPSS statistics 26 for windows application, the results obtained were Sig. (2-tailed) of 0.000. This shows that the Sig (2-tailed) value is <0.005. So it can be concluded that there is a significant influence of the Teams Games Tournament (TGT) learning method on student learning outcomes in Islamic Religious Education subjects.